Cover Image, Volume 37, Issue 6. (June 2017) - Fiorentino, Francesco; Bono, Sara; Pizzuti, Francesca; Duca, Sara; Polverari, Arianna; Faieta, Monica; Baldi, Marina; Diano, Laura; Spinella, Francesca
Abstract : Genome‐wide cell free DNA analysis allows prenatal identification of clinically relevant imbalances. From Fiorentino et al ., Prenat Diagn 37 : 593‐601, DOI:10.1002/pd.5053 .